Law For Space Travel: Analysis of Fiqh in Space - Hyder Gulam (IAIN Padangsidimpuan, 2023)
The purpose of this research discussion paper is to understand the Islamic issues involved in Space Travel, which is a novel field. Hitherto, only limited research has been undertaken on how Muslim astronauts can maintain their Islam for a prolonged period away from the Earth. This paper will commence with an introduction to Islamic law (which includes the distinct term fiqh), before discussing the obligations of Muslims in space. Also discussed in this paper will be the Maqasid, or higher objectives, which provides an avenue for Muslim space travelers to maintain their Islam within the framework of the religion. The methodology used in this paper is based on research of existing literature, comments from previous Muslim astronauts as well as a review of Muslim law that pertains to travel. The finding of this paper sets out the application of Islamic Law for interstellar Space Travel and off-world colonisation. It discusses the relevant ibadah rulings (literally meaning religious rituals such as prayer, fasting, ablution, keeping halal, and death rites inter alia) and how these can be practically applied in the context of space travel. This paper also outlines the moral, legal and practical challenges faced by a Muslim undertaking Space Travel and discusses the relevant Islamic ‘knowledge’ that may assist in reconciling these issues. The term interstellar Space Travel and colonisation is used to refer to those activities that are performed away from the Earth, such as in the micro-gravity of space or on an off world colony i.e., Mars. This paper is unique from other published papers in the field as it contemplates off world habitation and not just a short-term sojourn into space. The research finding is that Islamic Law is able to adapt to the challenges of space by incorporating how early Muslims maintained their Islam while traveling long distances outside their home countries. This is an emerging area of study, so there is a dearth and scarcity of literature about Muslims in space written from a scholarly perspective. This paper intends to rectify this situation by providing a marker for other scholars and researchers to follow